Association Between Optimal Combination Pharmacotherapy and Survival After Stroke: A Registry and Pharmaceutical Dispensing Study - Kilkenny, Monique F; Dalli, Lachlan L; Kim, Joosup; Andrew, Nadine E; Sanfilippo, Frank M; Sundararajan, Vijaya; Dewey, Helen M; Grimley, Rohan; Thrift, Amanda G; Cadilhac, Dominique A (International Journal of Population Data Science, 2020)
Introduction To prevent further vascular events, prescribing of multiple classes of medications (antihypertensive, antithrombotic and lipid-lowering) is recommended in national clinical guidelines following ischaemic stroke. Objectives and Approach Using real-world data, we determined the association between optimal combination pharmacotherapy (supply of all three classes, “optimal pharmacotherapy”) and survival after stroke. We linked a cohort of patients with first-ever ischaemic stroke from the Australian Stroke Clinical Registry (2010-2014) with national pharmaceutical dispensing and national mortality data. Cox regression was used to determine associations between pharmacotherapy in the first 30 days of stroke with 1-year (from day 31 to 395) all-cause mortality. All analyses were adjusted for socio-demographic (age, sex) and clinical characteristics (stroke severity, discharge destination). Results Among 6684 patients discharged following first-ever ischaemic stroke (median length-of-stay 5 days), 6466 patients who survived to 30 days were included (44% female, median age 74 years). During the first 30 days from discharge, 71.4% received ≥1 medication class, and 32.9% (n=2125) received optimal pharmacotherapy. Patients with optimal pharmacotherapy were older (≥75 years 50.3% vs <75 years 44.5%; p<0.001), discharged directly home (home 58.5% vs other 40.3%; p<0.001) and experienced a less severe stroke (able to walk on admission 46.9% vs 36.4%; p<0.001), than those without optimal pharmacotherapy. Between day 31 and 395, there were 667 deaths; 530 related to cardiovascular disease. Compared to no medication, treatment with two medications was associated with a 42% lower risk of death (hazard ratio [HR]: 0.58; 95%CI: 0.45-0.73); and optimal pharmacotherapy had a 62% lower risk of death (HR: 0.38; 95% CI: 0.31-0.47). Survival was similar between those with one or no medication. Conclusion / Implications Patients with ischaemic stroke who received optimal pharmacotherapy within 30-days of admission had greater one-year-survival. Further research is required to understand reasons for sub-optimal pharmacotherapy in these patients.